Post nephrectomy renal function: donor nephrectomy vs. radical nephrectomy - Tadić, Jelena; Rančić, Nemanja; Obrenčević, Katarina; Radojević, Milorad; Marić, Predrag; Tomić, Aleksandar; Petrović, Marijana (Vojnosanitetski pregled, 2022)
Background/Aim. Monitoring the renal function following donor nephrectomy (DN) or radical nephrectomy (RN) due to kidney tumors is considered essential. The aim of this study was to compare pre-operative and post-operative renal function in patients who underwent DN in relation to patients who underwent RN due to renal malignancy. Methods. A retrospective case-control study was performed, which included 199 patients divided into two groups: group 1 (105 patients) were patients who underwent DN due to living-related/unrelated kidney transplantation, while group 2 (94 patients) was a control group, and included patients who underwent RN due to clear cell renal cell carcinoma in the T1bNoM0 clinical stage, where this surgical procedure was the final form of treatment. Results. Pre-operative estimated glomerular filtration rate (eGFR) according to the Chronic Kidney Disease−Epidemiology Collaboration (EPI) equation (eGFR EPI) in the DN group was 94.95 mL/min/1.73 m2, while in the RN group, it was 71.00 mL/min/1.73 m2. Patients who underwent RN tended to have eGFR EPI below 60 mL/min/1.73 m2 after ten years of follow-up compared with patients who underwent DN. In the DN group, the average eGFR EPI was 80.40 mL/min/1.73 m2, and in the RN group, it was 56.00 mL/min/1.73 m2. A higher incidence of diabetes mellitus (DM) and arterial hypertension (AH) was also observed in the DN group of patients compared to the RN group (AH: 44.3% vs. 21.3%; DM: 22.6% vs. 9.6%, respectively). Conclusion. Comparative monitoring of these two groups showed that in both groups, the recovery of the renal reserve was achieved one year after nephrectomy due to the known adaptive mechanisms. Even though the initial renal reserve in a kidney donor is reduced after living kidney transplantation (nephrectomy, permanent loss of renal mass), kidney donors recover kidney function within the first year after surgery due to the adaptive mechanisms.